Framing, Separatist Agitation and the Nigerian State: A Study of the Indigenous People of Biafra (IPOB) - NIMFEL, Cirman Elisha; ANJIDE, Solomon Timothy (Socialscientia: Journal of Social Sciences and Humanities, 2023)
There has been a longstanding agitation in the South-East Nigeria for the break-up of Nigeria. This desire has been motivated by both individuals and groups. Groups such as the Movement for the Actualization of the Sovereign State of Biafra (MASSOB) and the Biafran Zionist Movement (BZM) have been influential in promoting the idea for the Biafran State, yet these groups have been weakened over time by internal rift and the might of the Nigerian state. Moreover, some of the movements have become moribund while others have been struggling for legitimacy. IPOB is a neo-separatist movement with increasing legitimacy regardless of the efforts of the Nigerian government to suppress its activities considered threat to national security. This study employs the framing theory to examine the logic of the IPOB campaigns and its supporters. The theory highlights the tripod relationship between IPOB, its narratives, and supporters, and the reasons such narratives are emotionally appealing and compelling enough to trigger collective action and sympathy for a common course. This study employs broad sources of data including peer-reviewed journals, official documents and, media sources. It concludes that IPOB enjoys mass following because of its strategic logic of creating quality framing and the ability to align its propaganda with its audience. This paper recommends the need for good optics of governance to counter the narratives of IPOB and the need for negotiated political solutions with the leadership of IPOB and relevant stakeholders.